The Impact of Debt Capacity on Firm’s Growth: (A Case Study of Selected Firms from Pharmaceutical Industry in Pakistan) - IHTESHAM KHAN; SYED WAQAR AHMAD SHAH; ASAD KHAN (Journal of Business & Tourism, 2021)
The ultimate goal of all activities within organizations is to achieve higher growth and finding new sources for mounting firm capital. This study aims to investigate debt capacity as the source of firm capital and its impact on firm’s growth. The objectives of this research to shows the relationship between market to book ratio and debt to asset ratio. Multiple liner regression is used between Growth and book leverage. By selected pharmaceutical sector that has been listed at Karachi stock exchange in Pakistan. In this research 8 companies are selected that are listed at Karachi Stock Exchange during the period of 2005-2014. In this paper secondary data is used. The result reveals a significant positive relationship between the debt to asset ratio and market to book ratio and debt to asset ratio. It displays that there is no negative effect of debt capacity on firm’s growth.